1989
DOI: 10.1002/bip.360281103
|View full text |Cite
|
Sign up to set email alerts
|

A CD determination of the α‐helix contents of the coat proteins of four filamentous bacteriophages: fd, IKe, Pf1, and Pf3

Abstract: The CD spectra of four filamentous bacteriophages--fd, IKe, Pf1, and Pf3--were analyzed to determine the alpha-helix contents of their major coat proteins. Measured spectra included the 192-nm band so that analyses could be carried out over the full wavelength range of the reference spectra for protein secondary structures available (a) from globular proteins [J.T. Yang, C.S.C. Wu, and H.M. Martinez (1986) Methods in Enzymology 130, 208-269] and (b) from poly(L-lysine) [N. Greenfield and G.D. Fasman (1960) Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 28 publications
3
39
1
Order By: Relevance
“…The protein model that we use here is 100% a-helix, consistent with some spectroscopic experiments (Clack & Gray, 1989), but some variations in the secondary structure may appear as further evidence is accumulated. The last few residues at either end might have i to i + 3 or i + 5 rather than a-helix (i to i + 4) hydrogen-bonding patterns, as sometimes found in globular proteins (Baker & Hubbard, 1984).…”
Section: Discussionsupporting
confidence: 82%
“…The protein model that we use here is 100% a-helix, consistent with some spectroscopic experiments (Clack & Gray, 1989), but some variations in the secondary structure may appear as further evidence is accumulated. The last few residues at either end might have i to i + 3 or i + 5 rather than a-helix (i to i + 4) hydrogen-bonding patterns, as sometimes found in globular proteins (Baker & Hubbard, 1984).…”
Section: Discussionsupporting
confidence: 82%
“…There have been numerous x-ray fiber diffraction studies of filamentous bacteriophages (3,(13)(14)(15)(16)(17), and although the resulting protein structures have relatively low resolution, these studies provide crucial information about the symmetry and packing of the coat protein subunits (15,18). Other spectroscopic investigations (19)(20)(21), as well as our earlier solid-state NMR studies (22)(23)(24)(25)(26), demonstrate that the coat protein is nearly all ␣-helix, its positively charged C-terminal residues are buried on the interior of the particle where they interact with the DNA, and the N-terminal residues are mobile (26) and exposed on the exterior of the virus particles.…”
mentioning
confidence: 99%
“…8a), with the 222-nm band about 1.4 to 1.5 times more intense than the shoulder at 208 nm (Ikehara et al, 1975;Nozaki et al, 1976;Day and Wiseman, 1978;Clack and Gray, 1989;Arnold et al, 1992;Roberts and Dunker, 1993). Oxidation with N-bromosuccinimide (NBS) suggested that the one tryptophan out of 50 residues of the major coat protein was responsible for the atypical CD spectrum (Day and Wiseman, 1978).…”
Section: B Implications For Estimates Of Protein Secondary Structurementioning
confidence: 99%